What Are The Risk Factors For Chronic Pain In Different Age Groups Of Stroke Survivors? : A Systematic Review - Stivenson Tiven; Daniel Siagian; Gabriela Leonila Yulianti Watilay (International Medical Journal Corp. Ltd, 2025)
Introduction: Stroke is a leading cause of long-term disability, with chronic pain being a significant and debilitating consequence that affects survivors' quality of life. The risk factors for developing chronic post-stroke pain appear to vary with age, creating challenges for clinical management. This systematic review aims to identify and categorize the age-specific risk factors for chronic pain in young, middle-aged, and elderly stroke survivors. Methods: A systematic search of PubMed, Semantic Scholar, Springer, and Google Scholar was conducted using PRISMA guidelines. Inclusion criteria focused on observational studies and systematic reviews assessing risk factors for chronic pain (persisting ≥3 months) in stroke survivors. Out of 1,309 records identified, 18 studies were included after screening and eligibility assessment. Data on study design, sample characteristics, pain assessment, and risk factors were extracted and synthesized. Results: For middle-aged survivors, risk factors included stroke severity, non-thalamic stroke location, sensory and motor impairments, neglect syndrome, female gender, and longer time since stroke. In elderly survivors, older age itself and thalamic stroke location were the primary predictors of persistent pain. No specific risk factors were reported for young adult stroke survivors. Younger patients showed better pain relief in response to neuromodulation therapies. Discussion: The evidence indicates that risk factors are age-dependent, though findings are most robust for the middle-aged population due to the composition of study samples. The lack of data for young adults represents a significant gap in the literature. The psychosocial impact of pain is severe across all ages, necessitating integrated care. Conclusion: Risk factors for post-stroke chronic pain differ significantly by age group. While a clear profile exists for middle-aged and elderly survivors, there is a critical lack of information for young adults. An age-aware, personalized approach to pain management is essential, and future research must focus on closing the knowledge gap for younger survivors.